Strategic Focusing of PT. XYZ Business to Strengthen Its Competitiveness - Adisuwondo, Anityo Yusman; Toha, Mohamad (The Indonesian Journal of Business Administration, 2012)
Rapidly growing information technology industry in Indonesia has caused the business competition to be competitive. PT. XYZ as one of information technology companies faced a new problem related with their competitiveness that have seen from business process, organization structure, and product variation they produced.To optimize PT. XYZ’s competitiveness, this research adopt Michael E. Porter Competitive Advantages framework which is to win the competition by using competitive advantages and competitive strategies. In addition, also use Business Model Canvas to strengthen its competitiveness. Focusing business as the competitive advantages analyzed by using forecasting method and formulate competitive strategies by using generic strategy based on business focus that have been determinate earlier. This research would give a business solution for PT. XYZ to focusing business to run and the right competitive strategies that been elaborate at determining customer segment to strengthen its competitiveness in information technology industry. In the end, this research would generate ideal business model as a business solution and its implementation strategy. An action plan to strengthen its business model is formulated in three steps, which are: improve its customer segments and its building block constructed, improve its value proposition and its building block constructed, and improve overall business model. In the end, the improvements include shifting the company’s focus to Software Production company, and applying focus differentiation strategy that focus on general products and non-system corporate segments. All the changes are outlined in a business model canvas that is expected to strengthen PT. XYZ competitiveness in the future. Keywords: Competition, competitive advantages, competitive strategies, business model, information technology